EVALUASI KEBIJAKAN PEMBANGUNAN MENARA TELEKOMUNIKASI PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN PARIGI MOUTONG - Patu, Serly (Katalogis, 2015)
This research aims at finding out how technical propriety dimension, financial and economic opportunity, political viability, and administrative viability in the evaluationof the policy of telecommunicationtower construction at the Department of Transportation, Communication, and Informatics in Parigi Moutong Regency using Bardach theory. This is a qualitative research with 7 informants taken by using a purposive sampling technique. The result of this research indicates that the evaliationof Policy of Telecommunication, and Informatics in Parigi Moutong Regency viewed from the technical viability dimensions; the Local Government is less serious to implement Cell Plan which has been made and there is no clear socialization in reporting the performance of management and supervision of surrounding; of economic and financial possibility dimension; all citizens can take pleasure in telecommunication provider in socializing rules, however giving positive impacts to the citizens like telecommunication service provisioning and providing employment to the citizens; and Administrative Viability dimension; the role of each sector or SKPD in coordinating among departments has run well but its supervision has not run well.